2016
DOI: 10.5194/adgeo-42-83-2016
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between tuna catch and variable frequency oceanographic conditions

Abstract: Abstract. Skipjack (Katsuwunus pelamis), yellow fin (Thunnus albacares) and albacore (Thunnus alulunga) tunas landed in the Eastern Pacific Ocean (EPO) countries and Ecuador were correlated to the Indexes Oceanic El Niño (ONI) and Multivariate Enso Index (MEI). The temporal series 1983–2012, and 1977–1999 (warm Pacific Decadal Oscillation, PDO), and 2000–2012 (cold PDO) were analyzed. Linear correlation showed that at least 11 % of the total landings were associated with the MEI, with a slightly negative gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…As a result, the quantitative oscillations of the catch reflect more directly the abundance and occurrence of the resource. Indeed, landings declined with an increase in the NOI, similarly to the findings of Ormaza-González et al (2016). Without the use of ENSO indexes, the different attributes of which are not discussed here, Hafiz and Anderson (1994) found that abrupt drops in skipjack catches by the Maldivian fleet were correlated with El Niño years.…”
Section: El Niño Southern Oscillationsupporting
confidence: 61%
See 1 more Smart Citation
“…As a result, the quantitative oscillations of the catch reflect more directly the abundance and occurrence of the resource. Indeed, landings declined with an increase in the NOI, similarly to the findings of Ormaza-González et al (2016). Without the use of ENSO indexes, the different attributes of which are not discussed here, Hafiz and Anderson (1994) found that abrupt drops in skipjack catches by the Maldivian fleet were correlated with El Niño years.…”
Section: El Niño Southern Oscillationsupporting
confidence: 61%
“…A negative NOI indicates the occurrence of El Niño, while the opposite is associated with La Niña. Median yearly catch values were calculated for the time series and then plotted against the NOI indices for the same year, based on the methodology proposed by Ormaza-González et al (2016). Polynomial regression curves were obtained using locally estimated scatterplot smoothing (LOESS), and R-squared values were calculated from the curve parameterization.…”
Section: El Niño Southern Oscillationmentioning
confidence: 99%
“…Around 44 % (2009–2016) of tuna captured in the eastern Pacific Ocean is skipjack ( Ormaza-González et al., 2016 ; IATTC, 2018 ), particularly along the equatorial line (outside of marine reserves) that roughly covers from 80–150W, 10N–20S ( Figure 3 ). In this area the biogeochemistry de Hg, Cd and Pb has not been determined yet, however, concentrations of some ocean regions can be found in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Environmental impact is huge in terms of diluvial rain episodes [3], release of gases to the atmosphere as their solubility decreases because the sea surface temperature (SST) increases nutrient depletion [4] and reduction of photosynthesis [5]. The whole marine trophic chain is negatively affected: this include important fish stocks as small and big pelagic fish [6,7]. El Niño [8,9] is a relatively low frequency (inter-annual) and non-cycled oceanographicatmospheric coupled process whose definition is referred to the area Niño 3.4 ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%